Bahasa Sebagai Sarana Berfikir Ilmiah - Rejeki, Wiwik Wiji (MKKS SMA, MKKS SMP se-Kota Metro, Persatuan Sarjana Pendidikan Islam Wilayah Provinsi Lampung, dan CV.IQRO Penerbitan, 2017)
Language is many things a system of communication, a medium for thought, a vehicles for literary expression, a social institution, a matter for political controversy, a factor in nation building. All normal human beings speak at least one language, and it is hard to imagine much significant social or intellectual activity taking place in its absence. Each of us, then, has stake in understanding how language is organized and how it is used. This article provide how to make language as scientific thinking facility in our life and expalining about the functions, the purposes and identity of our language. Because our language is different with animal language or other languages.